Celowość tworzenia i wdrażania koncepcji organizacji uczącej się - wyniki badań - Stańczyk-Hugiet, Ewa (Purposefulness of Creating and Developing Learning Organization Concept - Research Outputs, 2006)
Presented paper shows research output, the aim of which was to conclude recommendations of learning organization model are implemented. This research shows that 2/3 of researched organizations positively assess purposefulness of creating and developing learning organization concept. So, it is possible to formulate a thesis that learning organization concept is most valuable in sector with high rate of growth.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 205-210